2020
DOI: 10.1111/nph.16922
|View full text |Cite
|
Sign up to set email alerts
|

Axenic in vitro cultivation of 19 peat moss (Sphagnum L.) species as a resource for basic biology, biotechnology, and paludiculture

Abstract: Sphagnum farming can substitute peat with renewable biomass and thus help mitigate climate change. Large volumes of the required founder material can only be supplied sustainably by axenic cultivation in bioreactors. We established axenic in vitro cultures from sporophytes of 19 Sphagnum species collected in Austria,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 72 publications
(129 reference statements)
1
31
1
Order By: Relevance
“…In contrast, the productivity of S. squarrosum was on an average with that medium. This correlates with the findings of Heck et al (2021), who reported that the nutrient composition of the standard Sphagnum medium is suboptimal for some Sphagnum species and has to be improved further.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, the productivity of S. squarrosum was on an average with that medium. This correlates with the findings of Heck et al (2021), who reported that the nutrient composition of the standard Sphagnum medium is suboptimal for some Sphagnum species and has to be improved further.…”
Section: Resultssupporting
confidence: 90%
“…(2015) with regard to S. palustre productivity, and tested for four other Sphagnum species. However, this medium was not optimized for biomass production for the 19 Sphagnum species tested by Heck et al . (2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations